Husband-Wife Support Relations in Muslim Households: An Islamic Legal Analysis of Economic Practices Families in Wora Village, Bima Regency, West Nusa Tenggara - Yani, Ahmad; Ahlan, Ahlan (LPPPIPublishing, 2025)
This article aims to analyse the relationship between husband and wife in Muslim households with regard to financial support, highlighting the compatibility between Islamic legal norms and family economic practices in Wora Village, Bima Regency, West Nusa Tenggara. The study focuses on how the economic role of wives is practised, negotiated, and interpreted in household life, as well as how it is positioned within the framework of financial obligations according to Islamic law. This study uses a qualitative method with a juridical-empirical approach, in which data is obtained through in-depth interviews with married couples, religious leaders, and community leaders, supported by observations and a study of literature on fiqh related to the concept of financial support. Data analysis is carried out descriptively and analytically by linking field findings to the principles of Islamic law. The results of the study show several key findings. First, the obligation of nafkah is still normatively understood as the responsibility of the husband, as confirmed in classical fiqh. Second, in socio-economic practice, wives contribute to meeting family needs through various productive activities, both in the domestic and public sectors. Third, the economic contribution of wives is generally understood as a form of family cooperation and solidarity, not as a transfer of the obligation of nafkah from the husband to the wife. Fourth, the relationship of nafkah in Wora Village shows flexible and contextual role negotiations, influenced by economic factors, local culture, and the community's religious understanding. These findings confirm that family economic practices are not always contrary to Islamic law, as long as the principles of justice, willingness, and moral responsibility are upheld.